Sistem Pengawasan Berbasis IoT pada Robot Vision Untuk Peningkatan Keamanan Perimeter di Industri Batam - Caniago, Deosa Putra; Muhammad Jufri; M Abrar Masril (AI Society & STMIK Indonesia, 2024)
Batam City faces significant security challenges alongside rapid industrial growth, making the need for effective surveillance systems in industrial areas urgent. This research developed a surveillance robot utilizing Internet of Things and computer vision technologies to enhance perimeter security in industrial zones. The robot is equipped with Arduino as the controller, a Pixy2Cam camera for object detection, and a WiFi module for remote connectivity. Testing results indicate that the robot can detect individuals wearing safety gear in 0.2 seconds and achieves a detection success rate of 100% under ideal conditions. The developed controller application using MIT App Inventor also displays real-time images, allowing for rapid responses to potential threats. This research demonstrates that the developed surveillance robot effectively enhances monitoring in the Batam industrial area.